IMPLEMENTATION LEVEL OF OFFICE MANAGEMENT AND PERFORMANCE OF ADMINISTRATIVE PERSONNEL AT MTS MADANI KAB. GOWA - Marjuni,; Nurwahidah,; Mardhiah, (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The purpose of this study was to: describe the level of application of office management and the level of performance of administrative staff at MTs Madani Alauddin, Gowa Regency. The type of research used is quantitative research with descriptive methods, and uses a management approach. The data collection method used a questionnaire distributed to 15 respondents. The data analysis technique used is descriptive statistical analysis. The results of this study indicate that the level of application of office management is in the medium category. Likewise, the performance level of administrative staff at MTs Madani is also in the medium category. The implications of this research are expected for madrasas so that in the future they can implement office management effectively and efficiently, in order to support the performance of administrative staff so that they have better performance than before. The implementation of office management in question includes planning for office work along with standard operating procedures, clear job descriptions contained in the organizational structure, providing training on office work procedures, as well as evaluating and evaluating work with rewards. As for administrative staff, in order to improve their competence, motivation and discipline so that they can achieve maximum performance.